PENINGKATAN HASIL BELAJAR PESERTA DIDIK KELAS III-A MATERI ENERGI DAN PERUBAHANNYA PELAJARAN BAHASA INDONESIA MELALUI MODEL PEMBELAJARAN TEAM QUIZ PADA SDN MANUKAN KULON II / 499 SURABAYA - Zulfiana Zulfiana; Mintohari Mintohari; Wandik Wandik (EDUCATIONAL JOURNAL : General and Specific Research, 2023)
This objective reveals the learning outcomes of students in Indonesian subjects with the Quiz Team Learning Model. Learning Indonesian at school is often considered a boring lesson because it is full of lots of story text. The research method used is descriptive qualitative and quantitative. This research is a classroom action research with three cycles. The subjects of this study were class III-A students at SDN Manukan Kulon II / 499 Surabaya, totaling 26 students with details of 10 male students and 16 female students. The use of data collection techniques consists of observation techniques, learning achievement tests, and field notes during learning activities. There was an increase from cycle I to cycle II and cycle III in teacher activity and students' Indonesian learning outcomes with the percentage results being teacher activity in cycle I of 63.04%, cycle II of 72.82%, and cycle III of 94 .56%. The learning outcomes of students classically increased in cycle I by 61.61, in cycle II by 76 and in cycle III by 92.15. Learning completeness also increased in cycle I by 23%, cycle II by 81%, and cycle III by 88%. From the results of the classroom action research conducted by the researchers, it was concluded that the Quiz Team learning model can improve learning outcomes in Indonesian language lessons on energy and changes in class III-A students at SDN Manukan Kulon II / 499 Surabaya for the 2022/2023 Academic Year.